Adverse Drug Reactions with First-Line and Second-Line Drugs in Treatment of Tuberculosis - Prasad, Rajendra; Singh, Abhijeet; Gupta, Nikhil (Annals of the National Academy of Medical Sciences (India), 2021)
Drug-susceptible tuberculosis (DS-TB) requires treatment with first-line drugs (FLDs) whereas drug-resistant TB (DR-TB) are treated with combination of second-line drugs (SLDs) and fewer FLDs. Adverse drug reactions (ADRs) to these drugs are quite evident as they are being used for longer duration. The overall prevalence of ADRs with FLDs and SLDs are estimated to vary from 8.0 to 85 and 69 to 96%, respectively. Most ADRs are observed in the intensive phase as compared to continuation phase. Major concerns exist regarding treatment of DR-TB patients, especially with SLDs having lower efficacy more toxicity and high cost as compared to FLDs. A variety of ADRs may be produced by anti-TB drugs ranging from mild or minor to severe or major like gastrointestinal toxicity (nausea/vomiting, diarrhoea, and hepatotoxicity), ototoxicity, neurotoxicity (peripheral neuropathy and seizures), nephrotoxicity, cutaneous toxicity, and cardiotoxicity. Most of ADRs are minor and can be managed without discontinuation of treatment. Few ADRs’ can be major causing life-threatening experience leading to either modification or discontinuation of regimen and even mortality. A careful monitoring of ADRs during the treatment with anti-TB drugs and early recognition and appropriate management of these ADRs might improve adherence leading to favorable outcome.
Keywords: tuberculosis; adverse drug reactions; drug-resistant TB; drug-sensitive TB; first-line drugs; second-line drugs; anti-TB drugs